The Potential of Cistus salviifolius L. to Phytostabilize Gossan Mine Wastes Amended with Ash and Organic Residues - Carvalho, Luisa C. (2022)
The São Domingos mine is within the Iberian Pyrite Belt, a mining district with large concentrations of polymetallic massive sulfide deposits. Mine waste heaps are considered extreme environments, since they contain high total concentrations of potentially hazardous elements (PHE), which contribute to inhibiting the development of most plants. Autochthonous plant species, such as Cistus salviifolius L., are able to grow naturally in this degraded environment, and may contribute to minimizing the negative chemical impacts and improving the landscape quality. However, the environmental rehabilitation processes associated with the development of these plants (phytostabilization) are very slow, so the use of materials/wastes to improve some physicochemical properties of the matrix is necessary in order to speed up the process. This work studied the effectiveness of the phytostabilization with C. salviifolius of gossan mine wastes from the mine of São Domingos amended with organic and inorganic wastes in order to construct Technosols. The mine wastes have an acid pH ( 3.5), high total concentrations of PHE and low concentrations of organic C and available nutrients. The best vegetative development occurred without visible signs of toxicity in the Technosols containing a mixture of agriculture residues. These treatments allowed the improvement of the soil-plant system providing a better plant cover and improved several chemical properties of mine wastes, helping to speed up the environmental rehabilitation